The Soundscape of Klaipėda (II): An Auditioned City - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2017)
This article deals with urban soundscapes. A soundscape is a sonic environment and a multitude of sound sources that reach the human ear. By comparing different ways in which Klaipėda’s soundscape is constructed, we seek to analyze the aural background of Klaipėda. The research is based on the methodological distinction between hearing and listening. The first is a passive reception of sound, while the latter is interpreted as an activity consisting of both the search for sounds as well as their interpretation and analysis. The first article (Gedutis 2016) analyzed the Klaipėda soundscape as it can be heard. The current article concentrates on active attempts to listen to the city (or audition it), i.e., on the perception of the Klaipėda soundscape and the ways it is recorded, constructed and communicated by sound artists and theorists.